Isolation and characterization of the Mason-Pfizer monkey virus p12 protein - Knejzlík, Zdenek; Strohalm, Martin; Sedlácková, Lenka; Kodícek, Milan; Sakalian, Michael; Ruml, Tomás (Virology, 2004)
The Mason-Pfizer monkey virus (M-PMV) Gag protein, precursor to the structural proteins of the infectious virion, assembles into immature capsid-like particles when expressed at high levels in bacterial cells. Similar capsid-like particles can be obtained by in vitro assembly using a high concentration of isolated Gag. M-PMV Gag contains a p12 protein that has no corresponding analogues in most other retroviruses and has been suggested to contain an internal scaffold domain (ISD). We have expressed and purified p12 and the N- and C-terminal halves (Np12 and Cp12) that are predicted to be structurally independent domains. The behavior of these proteins was analyzed using chemical cross-linking, CD spectroscopy, and electron microscopy. The N-terminal half of p12 is largely alpha-helical although the C-terminal portion lacks any apparent ordered structure. Both p12 and Np12 form high-order oligomers in vitro and when expressed in E. coli produce organized structures that are visible by electron microscopy. Interestingly, Cp12, as well as the whole protein, can form dimers in the presence of SDS. The data show that both domains of p12 contribute to its ability to multimerize with much of this potential residing in its N-terminal part, most probably within the leucine zipper-like (LZL) sequence.
Keywords: sekvence aminokyselin; sekvenční seřazení; Escherichia coli; genové produkty gag; Leucine Zippers; Gene Products, gag; molekulární sekvence - údaje; dimerizace; leucinové zipy; Amino Acid Sequence; Sequence Alignment; Recombinant Proteins; Molecular Sequence Data; Dimerization; rekombinantní proteiny